PERSEPSI PESERTA DIDIK SEKOLAH MENENGAH ATAS DALAM PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 PADA MATA PELAJARAN SEJARAH - Mardiani Mardiani; Corry Corry; Ulung Napitu (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study aims to describe the perceptions of high school students in online learning during the COVID-19 pandemic in history subjects. The formulation of the problem in this study is how the perception of high school students in online learning during the COVID-19 pandemic is on the subject of history. The method in this research is a literature study. The results showed that students experienced problems related to signals during online learning. Most students have not mastered the application of learning well which affects the effectiveness of the learning process. There are still many students who find it difficult to understand the material with online learning. Students receive support from the school during online learning. The conclusion of this study is that the implementation of online learning during the COVID-19 pandemic experienced many obstacles based on the perceptions of students.